Association between C-reactive protein and hemoglobin in US rheumatoid arthritis patients based on NHANES data analysis - Liu, Defang; Yan, Jiao; Luo, Ting; Yang, Ling (Scientific reports, 2025)
The poor prognosis of rheumatoid arthritis (RA) and its potential for complications highlight the importance of understanding factors that are associated with incidence and mortality rates. The inclusion criteria of this study were RA-related data from 1999 to 2018 in the National Health and Nutrition Examination Survey (NHANES) dataset. Based on certain screening criteria, a total of 610 subjects were recruited. The Low CRP group (< 3 mg/L) and the High CRP group (> 3 mg/L) were significantly different in gender, poverty-to-income ratio, body mass index, hypertension, hemoglobin (Hb), hematocrit, and mean corpuscular hemoglobin. KM survival result revealed that male RA patients in the Low Hb group had a significantly lower survival rate than those in the High Hb group ( P < 0.0001), while female RA patients in the Low Hb group showed no statistically significant difference compared with the High Hb group ( P = 0.13). Importantly, there was a nonlinear relationship between Hb and all-cause mortality in RA patients. In this study, we identified Hb as a protective factor against CRP in RA patients and also observed its association with the prognosis of RA. Consequently, regulating Hb levels might be considered to be associated with the progression of RA.